2021
DOI: 10.1186/s12986-021-00565-0
|View full text |Cite
|
Sign up to set email alerts
|

Disease-associated metabolic alterations that impact satellite cells and muscle regeneration: perspectives and therapeutic outlook

Abstract: Many chronic disease patients experience a concurrent loss of lean muscle mass. Skeletal muscle is a dynamic tissue maintained by continuous protein turnover and progenitor cell activity. Muscle stem cells, or satellite cells, differentiate (by a process called myogenesis) and fuse to repair and regenerate muscle. During myogenesis, satellite cells undergo extensive metabolic alterations; therefore, pathologies characterized by metabolic derangements have the potential to impair myogenesis, and consequently ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 86 publications
0
9
0
Order By: Relevance
“…In chronic illness, there may be a chronic injury to the muscle depending on the severity and type of disease. Alterations in energy metabolism, inflammation, or restriction of movement can be factors that cause changes in satellite cells’ activity in diseased states [ 65 , 66 ]. Han et al reported that an increase in extracellular adenosine (eADO) in diabetic mice decreased the regenerative function of satellite cells [ 67 ].…”
Section: Discussionmentioning
confidence: 99%
“…In chronic illness, there may be a chronic injury to the muscle depending on the severity and type of disease. Alterations in energy metabolism, inflammation, or restriction of movement can be factors that cause changes in satellite cells’ activity in diseased states [ 65 , 66 ]. Han et al reported that an increase in extracellular adenosine (eADO) in diabetic mice decreased the regenerative function of satellite cells [ 67 ].…”
Section: Discussionmentioning
confidence: 99%
“…Muscle satellite cells are essential in skeletal muscle fibre regeneration and repair (42,43). In addition, a decline in satellite cell content has been hypoth-esised to be an important contributing factor in the development of skeletal muscle fibre atrophy in aging as well as various other myopathies (44,45). Although the muscle fibres of LDH patients clearly show more muscle fibre damage based on centrally located myonuclei, satellite cell content was not different compared with healthy controls.…”
Section: Discussionmentioning
confidence: 99%
“…Under the pressure of differentiation, myoblasts require more energy to maintain cell remodeling; accordingly mitochondria are constantly splitting in cells, and mitochondrial autophagy is markedly increased ( Hardy et al, 2016 ; Bloemberg and Quadrilatero, 2019 ). Mitochondrial renewal disorder has been repeatedly shown to reduce the differentiation ability of cultured myoblasts and the regeneration ability of skeletal muscle tissue ( Baechler et al, 2019 ; Joseph and Doles, 2021 ; Qualls et al, 2021 ). Enhancing mitochondrial biogenesis can improve muscle regeneration ( Niu et al, 2021 ).…”
Section: The Role Of Mitochondria In Myogenesis Regeneration and Musc...mentioning
confidence: 99%